2019
DOI: 10.1002/tcr.201800170
|View full text |Cite
|
Sign up to set email alerts
|

Base‐Mediated Transition‐Metal‐Free Dehydrative C−C and C−N Bond‐Forming Reactions from Alcohols

Abstract: In recent years, there has been an increasing interest in using alcohols as alkylating agents for C−C and C−N bond‐forming processes employing mainly TM‐catalysts. Although BH‐catalysis looks like a green atom economy process since water is the only by‐product, it often suffers from one or more drawbacks, such as the use of expensive noble metal complexes, capricious ligands, and toxic organic solvents. Therefore, straightforward, efficient, atom economy and environmentally benign alternative protocols are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 172 publications
2
17
0
Order By: Relevance
“…Furthermore, during reaction optimization studies, trace quantities of the secondary alcohol that would be generated via a MPV-type reduction of ketone 1 was observed, which supported the initial Oppenauer-type oxidation of secondary alcohol 2. 12 In line with these observations, and previous related investigations, 10,11 a plausible reaction mechanism would initiate with an Oppenauer-type alcohol oxidation followed by a selective cross-aldol condensation to form an enone intermediate (Scheme 2B). A subsequent Meerwein-Ponndorf-Verley (MPV)-type enone reduction would form the observed alkylation product.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, during reaction optimization studies, trace quantities of the secondary alcohol that would be generated via a MPV-type reduction of ketone 1 was observed, which supported the initial Oppenauer-type oxidation of secondary alcohol 2. 12 In line with these observations, and previous related investigations, 10,11 a plausible reaction mechanism would initiate with an Oppenauer-type alcohol oxidation followed by a selective cross-aldol condensation to form an enone intermediate (Scheme 2B). A subsequent Meerwein-Ponndorf-Verley (MPV)-type enone reduction would form the observed alkylation product.…”
supporting
confidence: 65%
“…Whilst investigating the use of alternative catalysts for this interesting and challenging transformation, control reactions revealed the presence of a significant base-mediated background reaction in the absence of any transition metal catalyst. 10,11 To this end, herein we report the first basemediated transition metal free a-C-alkylation of ketones using commodity secondary alcohols as alkylating agents.…”
mentioning
confidence: 99%
“…Acetaldehyde ( 10 ) was considered a possible intermediate and was reacted with benzyl alcohol under the same reaction conditions to give the desired product 3a in 12% GC yield (Scheme b). Furthermore, we confirmed that the aldol condensation path was used in the reaction by heating the respective aldehydes (instead of the alcohols) with no catalyst to produce the C2-extension alcohol 3a . Our stock reaction with benzyl alcohol was also performed using ethanol- d 6 .…”
supporting
confidence: 64%
“…This outlook will not cover related base-mediated alkylation processes, which have been reviewed previously. 16 ■ C−N BOND-FORMING PROCESSES N-Alkylation processes are a key facet of borrowing hydrogen chemistry, enabling alcohols (and amines) to be employed directly as alkylating agents in a diverse array of C−N bondforming reactions with various N-nucleophiles. The formation of N-benzylaniline from aniline and benzyl alcohol is the archetypal borrowing hydrogen reaction of this class and has been widely explored, with a plethora of literature examples.…”
Section: ■ Introductionmentioning
confidence: 99%